Examining the effect of a non-attendance fee on writing workshop attendance, grant submission, and success rates among K award applicants - Phillip A. Ianni; Brenda L. Eakin; Elias M. Samuels; Christine Byks-Jazayeri; Ellen Champagne; Matheos Yosef; Shokoufeh Khalatbari; Vicki L. Ellingrod (Journal of Clinical and Translational Science, 2025)
In 2009, the University of Michigan’s Michigan Institute for Clinical and Health Research developed a three-session K Writing workshop. Beginning in 2016, we implemented a non-attendance fee to encourage attendance across the three sessions. We examined whether this fee improved attendance, increased submission of an NIH K or R grant proposal, and improved success rates. Between 2012 and 2021, 373 participants attended the workshop. After the non-attendance fee was implemented, significantly more participants attended all three sessions of the workshop, and there was a statistical trend suggesting an increase in the success rate, while submission rates remained constant.